Interpersonal Communication Skills of Dyslexic Children and Implications for Guidance and Counseling Services - Hartanto, Dody; Barida, Muya; Setyowati, Arbin Janu; Saraswati, Fitri (Universitas Ahmad Dahlan, 2021)
Interpersonal communication skills are very important possessed by every individual. This study aims to examine how communication skills possessed by dyslexic children, given that dyslexic children experience language barriers. The study was conducted using a qualitative approach through the case study method of three students at Griya Baca Pelangi who had been diagnosed with dyslexia. Data was collected through observation, interview, and documentation techniques. Next, the data were analyzed with the concept of Miles and Huberman. The results were obtained that the dyspersic communication skills of dyslexic children differ. In guidance and counseling services, communication skills of dyslexic children can be improved through group guidance services and can also be combined with responsive services in the form of individual counseling or group counseling